A rehabilitation approach to the falls of geriatric patients - Marlena Kontowicz (Journal of Education, Health and Sport, 2019)
Abstract: Background: Falls of the elderly are not only in themselves one of the most common problems of geriatric patients, but also the cause of many complications that affect permanently or for a shorter period of time affect the quality of life of people over 65 years of age. These changes affect not only the efficiency and motility of the elderly but also may reduce self-esteem, limit social life or cause loss of self-confidence.